Donors' Participation in Iran's Health System: Challenges and Solutions - Ali Mohammad Mosadeghrad; Maryam Tajvar; Fatemeh Ehteshami (Kerman University of Medical Sciences, 2022)
Background  Philanthropic activities play an important role in health systems. Donors contribute to financing, generating resources, and providing healthcare services in Iranian health system. However, they face many challenges. This study aimed to identify barriers to donors' participation in the Iranian health system and to provide solutions.Methods  This qualitative study was performed using semi-structured interviews with 38 donors and 26 policy-makers and managers in the social affairs department of health ministry and medical universities in 2018. In addition, document analysis was performed and the relevant data were extracted. Thematic analysis was used for data analysis. All ethical considerations were followed in this research.Results  Insufficient structures, poor communications, low trust, ineffective working processes, bureaucracy, insufficient senior managers' support, weak legal support and poor monitoring were the most important challenges for donors' participation in the Iranian health system. Effective donor participation in the health system requires the creation of an appropriate system including the right structures, processes, culture, and management. The necessary changes must be planned, led and monitored to promote donors' participation in healthcare. A conceptual model was developed to strengthen donors' participation in the health system.Conclusion  Iranian donors face structural, procedural, cultural, and managerial challenges when financing the health system, generating resources, and providing health services. Policy-makers and managers should tackle these challenges and adopt strategies to reinforce donors' participation in the health system. Planning, organizing, leading, monitoring, evaluation, transparency, accountability, and a commitment to meet donors' needs are necessary for successful philanthropy initiatives in the health sector.